2013
DOI: 10.1007/s10862-013-9388-8
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of Psychopathy Predict Poorer Motor Control: Implications for Understanding the Psychopathy Construct

Abstract: A review of the literature suggests that higher levels of psychopathy may be linked to less effective behavioral control. However, several commentators have urged caution in making statements of this type in the absence of direct evidence. In two studies (total N = 142), moment-to-moment accuracy in a motor control task was examined as a function of dimensional variations in psychopathy in an undergraduate population. As hypothesized, motor control was distinctively worse at higher levels of psychopathy relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…Aberrant structure of this precentral area might suggest a similar impairment of motor functioning in both groups. Deficits in motor areas are consistently found in ASD ( Fournier et al, 2010 , Mosconi and Sweeney, 2015 , Nebel et al, 2014 ), but there is also evidence of functional and anatomical deviancies of motor cortex in psychopathy ( De Brito et al, 2021 , Robinson and Bresin, 2014 , Tillem et al, 2019 ). Similarly as mentioned before, there is evidence of abnormal growth trajectory of the ASD also in the motor cortex regions ( Mostofsky et al, 2007 , Riddle et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant structure of this precentral area might suggest a similar impairment of motor functioning in both groups. Deficits in motor areas are consistently found in ASD ( Fournier et al, 2010 , Mosconi and Sweeney, 2015 , Nebel et al, 2014 ), but there is also evidence of functional and anatomical deviancies of motor cortex in psychopathy ( De Brito et al, 2021 , Robinson and Bresin, 2014 , Tillem et al, 2019 ). Similarly as mentioned before, there is evidence of abnormal growth trajectory of the ASD also in the motor cortex regions ( Mostofsky et al, 2007 , Riddle et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results should be taken as modest support for our hypotheses, and allow for us to further discriminate secondary psychopathy from primary psychopathy. Previous research has revealed that, compared to primary psychopathy (emotionally stable psychopathy), secondary psychopathy (neurotic psychopathy) is a better predictor of uncontrolled behaviors such as substance abuse, aggression, and criminality [ 45 ]. Therefore, from a mental health perspective, skills in emotion regulation should be included when reckless eating behaviors are the focus of an intervention program.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of the VIM is thought to underpin psychopathy -a personality disorder characterised by atypical affect (e.g., callousness, low guilt, and poor empathy; Hare 2003) and behaviour (e.g., increased sensation seeking and aggression; Dawel, O'Kearney, McKone, & Palermo, 2012). In psychopathy, VIM deficiency is reflected through impaired processing of facial expressions of distress (e.g., fear and sadness; Dawel et al, 2012;Marsh & Blair, 2008;Wilson et al, 2011), coupled with poor motor extinction (Robinson & Bresin, 2014). While psychopathy occurs in fewer than 1% of the general population (Hare, 2003), associated personality traits, collectively referred to as callous-unemotional (CU) traits, are normally distributed and can be used to understand underpinning biological mechanisms, free from epiphenomena associated with a criminal lifestyle (Centifanti et al, 2016;Essau, Sasagawa, & Frick, 2006;Frick et al, 2000).…”
Section: Violence Inhibition Mechanism Functioning Mediates the Relatmentioning
confidence: 99%